2014
DOI: 10.1667/rr3819.1
|View full text |Cite
|
Sign up to set email alerts
|

In VivoEffects of Lattice Radiation Therapy on Local and Distant Lung Cancer: Potential Role of Immunomodulation

Abstract: Radiation is a potent immune-modulator that elicits cell death upon tumor, stromal and angiogenic compartments of tumor microenvironment. Here, we test a novel approach of high-dose radiation delivery using three dimensional volume based lattice radiation therapy (LRT) to understand the impact of different volume irradiation in eliciting both local and metastatic/distant tumor control through modulation of tumor immune micro-environment. To study such effects of LRT, tumors were implanted in both hind legs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 45 publications
4
94
0
Order By: Relevance
“…However, other clinical [8][9][10] and pre-clinical studies [11] have shown that immunotherapy was not required to induce RIAE. Furthermore, numerous in vitro studies [3,[12][13][14] have shown that a strong RIAE/RIBE can be induced by tumor signaling in response to radiotherapy, also without the immune system mediating the phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…However, other clinical [8][9][10] and pre-clinical studies [11] have shown that immunotherapy was not required to induce RIAE. Furthermore, numerous in vitro studies [3,[12][13][14] have shown that a strong RIAE/RIBE can be induced by tumor signaling in response to radiotherapy, also without the immune system mediating the phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The simulated results showed acceptable peak-to-valley dose differences can be achieved with the three different sizes of breast phantoms. [4][5][6][7][8] As the phantom size increases, the number of shots in the phantom also increase. There were 22, 75, and 172 shots total for the 10, 15, and 20 cm phantom diameters, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we chose a shot spacing of 3.5 cm in the sagittal planes and 3.0 cm in the coronal planes in order to achieve acceptable peaks-to-valley dose ratios. [4][5][6][7][8] A total of nine shots were delivered on a central vertical plane which created a 3 × 3 grid. A Monte-Carlo simulation of the nine shots with 15 mm collimators was also created for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, a study performed on mice has shown that the maximum growth delay and the strongest Th1 response is induced by irradiation of 20 to 50% of the tumor volume [70].…”
Section: Relations Between Radiotherapy and The Tme: Clinical And Researcmentioning
confidence: 99%